Insider versus outsider CEOs, executive compensation, and accounting manipulation - JONGJAROENKAMOL, Prasart (Institutional Knowledge at Singapore Management University, 2017)
This paper examines the role of the financial reporting environment in selecting a new CEO from within versus outside the organization. Weak reporting controls allow the CEO to misreport performance information, which reduces the board's ability to detect and replace poorly-performing CEOs as well as aggravates incentive contracting. We show that these adverse effects are stronger when the CEO is an outsider rather than an insider. Our model predicts that boards are more likely to recruit a CEO from the outside when the performance measures with which the new hire is assessed are harder to manipulate.